Le Carte Nautiche: dalla carta ai BIT - Caterino, Aldo (GEOmedia, 2019)
The Istituto Idrografico della Marina, founded in Genoa in 1872, is responsible for the national hydrographic service and the production of the official nautical documentation, both paper and digital, relating to Italian seas. Today the cartography is entirely produced with the help of the computer and sent to users in digital format or printed on special kinds of paper via digital machines: in short, the process has been strongly standardized and industrialized, losing part of the romantic and of craftsmanship aura it had in the past. The electronic cartographic portfolio published by the Istituto Idrografico consists of 262 charts and is splitted for navigation purposes, ranging from large-scale maps of Italian territorial waters, coasts and main ports, to small-scale maps covering all the Mediterranean and the Black Sea.